Physiotherapy plus conventional treatment versus conventional treatment only in the treatment of functional constipation in children: design of a randomized controlled trial and cost-effectiveness study in primary care - Jojanneke J. G. T. van Summeren; Gea A. Holtman; Yvonne Lisman- van Leeuwen; Lisa E. A. M. Louer; Alice H. C. van Ulsen-Rust; Karin M. Vermeulen; Boudewijn J. Kollen; Janny H. Dekker; Marjolein Y. Berger (BMC, 2018)
Abstract Background Our aim was to design a study to evaluate the effectiveness and cost-effectiveness of adding physiotherapy to conventional treatment for children with functional constipation in primary care. Physiotherapy is focusing on improving the coordination between the pelvic floor and abdominal musculature during bowel movement, while conventional treatment is mainly focusing on symptomatic relief of symptoms, therefore, we expect the effects of physiotherapy will be more sustainable than the effects of conventional treatment. In this paper we describe the final study design and how the design was adapted, to overcome recruitment problems. Methods We designed a randomized controlled trial of children aged 4-17 years with functional constipation diagnosed by a general practitioner or pediatrician. Children in the intervention group received physiotherapy plus conventional treatment, and those in the control group received conventional treatment only. Follow-up measurements took place at 4 and 8 months. The primary outcome was treatment success defined according to the Rome-III criteria as the absence of functional constipation, with no laxative use. Secondary outcomes were absence of functional constipation irrespective of laxative use, quality of life, global perceived effect, and costs. Children were recruited from September 2014 to February 2017. Initially, we aimed to include children with recent symptom onset. However, in the first phase of enrollment we were confronted with an unforeseen recruitment problem: many children and their parents refused randomization because physiotherapy was considered too burdensome for the stage of disease. Therefore, we decided to also include children with a longer duration of symptoms. In total 134 children were included. Discussion The target number of participants is achieved. Therefore, the results may change thinking about the management of functional constipation in children. Trail registration Netherlands Trial Register (NTR4797), registered 8 September 2014.